2020
DOI: 10.1039/d0ta07039d
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional molybdenum carbides: active electrocatalysts for the nitrogen reduction reaction

Abstract: The nitrogen reduction reaction (NRR) is a promising alternative method to the Haber-Bosch process to produce ammonia due to its mild reaction conditions. The efficiency of NRR is highly dependent...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Besides, Zhang et al. reported that two‐dimensional molybdenum carbides, 1T‐Mo 2 C, 2H‐Mo 2 C, and MoC 2 (100) have high performance with the highest reaction Gibbs free energy of 0.52, 0.86, and 0.63 eV, respectively, on NRR [71] . It can be seen that the alloy has satisfactory catalytic performance compared with some two‐dimensional Mo‐based materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, Zhang et al. reported that two‐dimensional molybdenum carbides, 1T‐Mo 2 C, 2H‐Mo 2 C, and MoC 2 (100) have high performance with the highest reaction Gibbs free energy of 0.52, 0.86, and 0.63 eV, respectively, on NRR [71] . It can be seen that the alloy has satisfactory catalytic performance compared with some two‐dimensional Mo‐based materials.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al. calculated the change in bond length and found that after N 2 being adsorbed on 2H‐Mo 2 C, the N−N bond length became 1.32 Å [71] . It was illustrated that molybdenum‐containing compounds can effectively activate N 2 molecules.…”
Section: Resultsmentioning
confidence: 99%
“…16 Several other Mo-based two-dimensional (2D) materials, nanoparticles and nanoclusters, single atom catalysts (SACs) and organometallic complexes have been reported as efficient catalysts for NRR. [17][18][19][20][21][22][23][24][25][26] While Mo-containing organic and inorganic complexes efficiently adsorb and form stable dinitrogen complexes, their application as electrocatalysts or electrodes are not warranted. 18 Mo clusters and SACs, on the other hand, require a conducting/semi-conducting support for further usage as electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…18 Mo clusters and SACs, on the other hand, require a conducting/semi-conducting support for further usage as electrocatalysts. 19,20,22,27 In this regard, Mo-based 2D materials such as MoS 2 , 24,[28][29][30][31] MXenes (Mo 2 C) [32][33][34] and MBenes (Mo 2 B 2 ) 35,36 are appealing electrocatalysts owing to their high electrical conductivity and presence of active Mo metal centres. These 2D materials not only show high hydrophilicity, stability and conductivity but are interesting from the catalytic aspect of nitrogen reduction as the Mo metal is accessible to the nitrogen molecule.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Among these promising candidates, Mo 2 C possesses outstanding HER property, as well as excellent electrochemical stability, which is regarded as a potential electrocatalyst towards HER due to low cost and good conductivity. [15,16] Furthermore, extensive synthetic methods have been reported, including controlling morphology and nanostructure, constructing hybrid structures, and introducing a second transition metal. [17,18] However, during these processes, solvent such as water, ethanol, and HCl solution are frequently applied in the process of preparation and posttreatment, most of which are harmful to the environment and increase the cost of final products.…”
Section: Introductionmentioning
confidence: 99%